2019
DOI: 10.5432/ijshs.201923
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Physical Education Preservice Teachers' Specialized Content Knowledge

Abstract: The purpose of the study was to investigate the levels of specialized content knowledge (SCK) in volleyball and basketball among preservice teachers (PSTs) in Japan. A total of 689 PSTs (female n = 258) participated in the study. Content maps were used to examine the levels of SCK and were analyzed using content development categories and a formula to calculate SCK index scores (Ward et al., 2017). An SCK index score of three was used to differentiate mature and immature levels of SCK. Participants' playing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Studies that analyzed the quantity of time allocated to CCK and SCK using syllabi reported that physical activity and sports courses are particularly focused on performance of the content (Dervent et al, 2020a; Ince et al, 2012; Kim et al, 2015; Ward et al, 2013). It is also known that performance has limited or almost no impact on the acquisition of knowledge of instructional tasks; rather, it is best acquired via explicit training focusing on SCK (Tsuda et al, 2019a, 2019b; Ward et al, 2018a, 2018b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that analyzed the quantity of time allocated to CCK and SCK using syllabi reported that physical activity and sports courses are particularly focused on performance of the content (Dervent et al, 2020a; Ince et al, 2012; Kim et al, 2015; Ward et al, 2013). It is also known that performance has limited or almost no impact on the acquisition of knowledge of instructional tasks; rather, it is best acquired via explicit training focusing on SCK (Tsuda et al, 2019a, 2019b; Ward et al, 2018a, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…Studies that analyzed the quantity of time allocated to CCK and SCK using syllabi reported that physical activity and sports courses are particularly focused on performance of the content (Dervent et al, 2020a;Ince et al, 2012;Kim et al, 2015;Ward et al, 2013). It is also known that performance has limited or almost no impact on the acquisition of knowledge of instructional tasks; rather, it is best acquired via explicit training focusing on SCK (Tsuda et al, 2019a(Tsuda et al, , 2019bWard et al, 2018aWard et al, , 2018b. Whether originating from task representations, skill execution, or a strategy, understanding the possible reasons for student errors is essential knowledge that enables teachers to design instructional tasks that will lead to student learning (Hare and Graber, 2000;Sadler and Sonnert, 2016).…”
Section: Relationship Between Instructors' Knowledge Of Student Error...mentioning
confidence: 99%
See 1 more Smart Citation